Karakteristik Bakteri Pendegradasi Bahan Pangan Asal Saluran Pencernaan Kecoa Amerika (Periplaneta americana) dari Pasar Tradisional - Dwiana Muflihah Yulianti; Arif Rahman Hikam; Trisnowati Budi Ambarningrum; Taruna Dwi Satwika; Dyah Fitri Kusharyati; Hilmiyah Al'alawiyah (Biotropic : The Journal of Tropical Biology, 2023)
American cockroach (Periplaneta americana) is one of the most common pests found in houses, apartments, and public facilities such as markets. As vector insects, cockroaches have symbiosis with microorganisms. Some of these microorganisms can live in cockroaches' cuticles and digestive tracts. Besides being able to pose a danger to human health, the microbes in cockroach bodies also have the potential to cause food damage. This study aimed to determine the diversity of microorganisms originating from the digestive tract of the American cockroach and their potential to cause food spoilage. The research was conducted in several stages: sampling cockroaches at a traditional market, isolating bacteria from the digestive tract of cockroaches, qualitatively testing amylolytic, proteolytic, and lipolytic potentials, and characterizing bacterial isolate by morphologically and biochemically character. The results showed that there were 26 isolates of bacteria isolated from the digestive tract of American cockroaches from the market, 62.96% of the isolates were found to have the ability to degrade protein, 37.04% of the isolates had the ability to degrade starch, and 40.74% of the total isolates can degrade fat. These isolates had various morphological and biochemical characteristics. Bacterial isolates derived from American cockroaches from traditional markets have the potential to degrade food.